Pendampingan Kegiatan BISAMU (Bina Sukses Akhlak Mulia) di SMK Darul Ulum Purwodadi - Fachrudin Yusuf, Wiwin; Adiputro, Muzammil; Faqih, Moch. Abdulloh (Lembaga Penerbitan dan Publikasi Ilmiah, 2025)
The Bina Sukses Akhlak Mulia (BISAMU) program at SMK Darul Ulum Purwodadi aims to develop students with religious and pious character. This program involves activities such as dhuha prayer, dhuhur prayer in congregation, reading the Qur'an, and religious social activities. This study aims to evaluate the effectiveness of the BISAMU program in instilling religious values in students. The method used is Habitual Guidance (HG), which involves habit identification, planning, mentoring and monitoring, adjustment and evaluation, and positive reinforcement. The results show a significant increase in religious knowledge and positive changes in students' behavior. This program has proven to be effective in creating a more religious and morally upright generation.